DETERMINANTS OF WOMEN PARTICIPATION IN LIVESTOCK PRODUCTION IN MANGU LOCAL GOVERNMENT AREA OF PLATEAU STATE, NIGERIA - Abdulhameed A. GIREI; E.G. ONUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper determined women participation in livestock Production in Mangu local government area of Plateau State, Nigeria. Simple random sampling was used to select 90 women livestock farmers. Descriptive statistics, Participation Index and Multiple Regression Analysis were employed to analyse the data. The regression results revealed that extension contact was significant (p<0.01) and positive, while age and education (p<0.01) and years of experience (p<.0.05) were significant factors influencing women participation in livestock production although negative. Poultry, swine and goat production raked first, second and third respectively. The result further shows that the coefficient of multiple determinations (R2) was 0.554, this indicates that 55.4% of the variation in women participation is accounted for by the explanatory variables included in the model. The study recommends that the women should be more capacitated in terms of support through engaging them more meaningfully on economic activities of not only the family but in decision making on matters affecting women. Also the training need of women participation in livestock production should be identified and also soft capital should be provided at the affordable and right time.